2015
DOI: 10.1371/journal.pone.0126176
|View full text |Cite
|
Sign up to set email alerts
|

TIPE2 Inhibits Lung Cancer Growth Attributing to Promotion of Apoptosis by Regulating Some Apoptotic Molecules Expression

Abstract: Recent studies found that TIPE2 was involved in cancer development. However, little is known about TIPE2 in lung cancer. Our study aims to clarify the role of TIPE2 in lung carcinogenesis. We examined the expression of TIPE2 in lung squamous cancer (LSC), small cell lung cancer and lung adenocarcinoma (AdC) tissues and found that TIPE2 expression was lost in small cell lung cancer, compared with adjacent non-tumor tissues. Overexpression of TIPE2 significantly inhibited the growth of lung cancer cell H446 in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 25 publications
1
40
1
Order By: Relevance
“…52 In neoplastic studies, TIPE2 expression has been found to be decreased or completely lost in human hepatic cancer, 23 and reduced TIPE2 expression is associated with metastasis. It is also downregulated in gastric cancer tissues, 53 NSCLC tumors 54 and small cell lung cancer tumors, 55 and the levels of TIPE2 inversely correlate with NSCLC TNM staging. 54 Moreover, reduced TIPE2 expression is associated with metastasis of hepatic cancer.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
“…52 In neoplastic studies, TIPE2 expression has been found to be decreased or completely lost in human hepatic cancer, 23 and reduced TIPE2 expression is associated with metastasis. It is also downregulated in gastric cancer tissues, 53 NSCLC tumors 54 and small cell lung cancer tumors, 55 and the levels of TIPE2 inversely correlate with NSCLC TNM staging. 54 Moreover, reduced TIPE2 expression is associated with metastasis of hepatic cancer.…”
Section: Tipe2 Is a Negative Regulator Of Immunity And Inflammationmentioning
confidence: 99%
“…The shRNA sequence was cloned into the GV102 vector with enhanced green fluorescent protein and the identity of the resulting construct was verified by sequencing. A549 and LTEP-a2 cells were transfected with shAnxa3 or control vector using Lipofectamine® 2000 transfection reagent (Life Technologies) and G418 was added to select the transfected cells as described previously [15]. The mRNA and protein levels of Anxa3 in all stably transfected cell lines were detected by quantitative PCR (qPCR) and western blotting, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Colony formation assay was performed as described in our previous study [15]. In brief, cells were seeded at a density of 500 cells per well in 6-well culture plates and cultured for about two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that both p38 MAPK and JNK activation promote cell apoptosis in tumour cells under some circumstances [53][54][55]. There is also extensive evidence showing that NF-κB activation suppresses apoptosis, most likely because NF-κB promotes the synthesis of proteins that can protect cells from apoptosis [56][57][58][59].…”
Section: Melatonin Enhances the Effectiveness Of Cisplatin By Suppresmentioning
confidence: 99%